PENGARUH CERAMAH ATAU CERITA PENTINGNYA IPA TERHADAP PENINGKATAN KECINTAAN MAHASISWA PADA IPA - Sudarto, Sudarto (Bajang Institute, 2025)
The aim of this study was to determine whether giving lectures or stories or views on the importance of science can or cannot influence the increase in students' love of science. This type of research is a pre-experiment with a One Group Pretest Posttest design. The respondents in this study were of the PGSD FIP UNM Campus VI Bone students who took the Basic Science Concepts course in the even semester of the 2024/2025 academic year in amount of 28 people. The data collection instrument used was a questionnaire sheet. The data analysis used was descriptive and inferential data analysis. Results: the average score of the level of students' love of science before giving lectures or stories about the importance of science was 6.68 and after giving lectures or stories about the importance of science was 9.29 and the sig. value for the Wilcoxon difference test = 0.000. Conclusion: giving lectures or stories about the importance of science to students has an effect on increasing students' love of science.